2017
DOI: 10.4067/s0718-95162017005000027
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cold stress resistance via free radical scavenging ability and promoted water status and photosynthetic capacity of gallic acid in soybean leaves

Abstract: Plant polyphenols exhibit a wide variety of biological activities such as antimutagenicity, anticarcinogenicity and antioxidative activity. There is no report whether gallic acid (GLA), a naturally occurring plant phenol, is able to activate the plant defense system under cold stress. For this purpose, after soybean (Glycine max) was hydroponically grown for 3 weeks, seedlings were treated with gallic acid (GLA; 1 and 2 mM) and cold stress (5 o C and 10 o C) and GLA and stress combination for 72 h. The inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…Interestingly, in a study on soybean leaves (Yildiztugay et al 2017) , the same result was observed, namely that there was no increase of SOD activity in stress-treated soybean leaves, although an increase of H 2 O 2 content was induced. As detected by Yildiztugay et al (2017), enhancement of H 2 O 2 content in stress-treated roots of soybean plants was related to increased NOX activity in their leaves. On the other hand, GLA application prevented the decline of SOD activity induced by stress.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, in a study on soybean leaves (Yildiztugay et al 2017) , the same result was observed, namely that there was no increase of SOD activity in stress-treated soybean leaves, although an increase of H 2 O 2 content was induced. As detected by Yildiztugay et al (2017), enhancement of H 2 O 2 content in stress-treated roots of soybean plants was related to increased NOX activity in their leaves. On the other hand, GLA application prevented the decline of SOD activity induced by stress.…”
Section: Discussionsupporting
confidence: 54%
“…However, in the present study, GLA did not contribute to elimination of the damage caused by cold stress through alteration of the reduced/oxidised GSH ratio under stress conditions. On the other hand, GLA application in soybean leaves treated with stress (5°C) activated the ascorbate-glutathione cycle (Yildiztugay et al 2017). These results suggest no apparent role for the ascorbate-glutathione cycle in damage alleviation by GLA in soybean roots under cold stress.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The level of lipid peroxidation called as thiobarbituric acid reactive substances (TBARS) was detected according to Yildiztugay et al [9].…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%
“…For determination of SOD isoforms and total SOD activity, the procedure was completed [8]. Analysis of CAT isozymes/activities was performed the procedure given by Yildiztugay et al [9]. POX isozymes, total POX activity, NOX isozyme and its activity were done [8,9].…”
Section: Determination Of Isozyme and Total Activity Of Some Enzymesmentioning
confidence: 99%